2012
DOI: 10.1186/1478-811x-10-39
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nef: a multifaceted modulator of T cell receptor signaling

Abstract: Nef, an accessory protein of the Human Immunodeficiency Virus type 1 (HIV-1), is dispensable for viral replication in cell culture, but promotes virus replication and pathogenesis in the infected host. Acting as protein-interaction adaptor, HIV-1 Nef modulates numerous target cell activities including cell surface receptor expression, cytoskeletal remodeling, vesicular transport, and signal transduction. In infected T-lymphocytes, altering T-cell antigen receptor (TCR) signaling has long been recognized as one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 118 publications
1
53
0
Order By: Relevance
“…The precise mechanism by which Nef promotes TNT formation in MDMs in an M-Sec-dependent manner also remains to be determined. It has been demonstrated that Nef affects various aspects of host cell vesicular transport and cytoskeletal dynamics (41,42). Indeed, WT virusinfected MDMs, but not DNef virus-infected MDMs, exhibited protuberant shapes (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism by which Nef promotes TNT formation in MDMs in an M-Sec-dependent manner also remains to be determined. It has been demonstrated that Nef affects various aspects of host cell vesicular transport and cytoskeletal dynamics (41,42). Indeed, WT virusinfected MDMs, but not DNef virus-infected MDMs, exhibited protuberant shapes (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy allows Nef to optimize viral replication in CD4+ T lymphocytes and at the same time disturb efficient antiviral immunity. 192 Measles virus (MV), a single-stranded, negative-sense, enveloped RNA virus also interferes with actin remodeling in T-cells. CD3/CD28-induced activation of the PI3K/AKT kinase pathway and proliferation is impaired in T cells upon contact with the measles virus glycoprotein (gp) complex.…”
Section: Interactions With the Immune Systemmentioning
confidence: 99%
“…In particular, we hypothesized that HIV-1 Nef, an Ïł27-kDa accessory protein that enhances viral pathogenesis, may play an early role in determining HIV-1 control. Nef interacts with a number of host proteins and performs multiple functions (33), including downregulation of cell surface CD4 (34) and HLA class I (35), upregulation of HLA class II invariant chain (CD74) (36), enhancement of virion infectivity (37), stimulation of viral replication in peripheral blood mononuclear cells (PBMC) (38), and alteration of T cell receptor (TCR) signaling (39,40). Nef's relevance to pathogenesis is illustrated by the exceptionally slow disease progression exhibited by individuals infected with nef-deleted or nef-defective HIV-1 (41)(42)(43)(44).…”
mentioning
confidence: 99%